Laporan Keuangan “Personal” Berdasarkan SAK EMKM dalam Kacamata Petani - Layly Dwi Rohmatunnisa (BAJ: Behavioral Accounting Journal, 2022)
The purpose of this research is to dig up information about the practice and how the understanding of farmers that in case it also works as a trader of fertilizer semi- organic about the recording of financial businesses farmer after a given training management and finance by a team of Program Partnership People who do by one of the lecturers at the State University in Indonesia. Analysis of the behavior of personal finance at farmer and trader of fertilizer and its relationship with the difference output reports finances that they produce, with Hermeneutic Intensionalism, this study concludes that farmers have different personal finance behaviors. The first considers that financial reporting is very difficult and only for macro entities. Second, financial reports are considered to be troublesome so that the recording process is only wishful thinking. Meaning that the third was reported finances only be incidental, by thus making of statements finance if dibutukan alone.